Yield reduction via the Knudsen layer effect in a mixture of fuel and pusher material. (6th December 2018) - McDevitt, Christopher J; Tang, Xian-Zhu; Guo, Zehua
Abstract: Hydrodynamic mix in inertial confinement fusion capsules produces chunk mix between deuterium–tritium fuel and inert pusher materials. The characteristic size of the intermingled fuel and pusher materials can be rapidly reduced by fluid mix, especially when the streamlines of the flow field are chaotic. This leads to an increasing Knudsen number for the fuel segments and a decreasing size of the pusher remnant with respect to the fuel ion mean-free-path. The former exacerbates Knudsen layer yield degradation due to fast ion losses, while the latter tends to alleviate Knudsen layer yield reduction due to other kinetic effects such as diffusive tunneling.